Westonci.ca offers fast, accurate answers to your questions. Join our community and get the insights you need now. Experience the ease of finding quick and accurate answers to your questions from professionals on our platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
To determine which function represents a parabola with zeros at [tex]\( x = -2 \)[/tex] and [tex]\( x = 4 \)[/tex], and a y-intercept at [tex]\( (0, -16) \)[/tex], we need to verify these conditions for each given function.
### Checking Zero Points
1. Function A: [tex]\( f(x) = 2x^2 + 4x - 16 \)[/tex]
- Calculate [tex]\( f(-2) \)[/tex]:
[tex]\[ f(-2) = 2(-2)^2 + 4(-2) - 16 = 2(4) - 8 - 16 = 8 - 8 - 16 = -16 \neq 0 \][/tex]
- Calculate [tex]\( f(4) \)[/tex]:
[tex]\[ f(4) = 2(4)^2 + 4(4) - 16 = 2(16) + 16 - 16 = 32 + 16 - 16 = 32 \neq 0 \][/tex]
- Thus, Function A does not have zeros at [tex]\( x = -2 \)[/tex] and [tex]\( x = 4 \)[/tex].
2. Function B: [tex]\( f(x) = x^2 - 2x - 8 \)[/tex]
- Calculate [tex]\( f(-2) \)[/tex]:
[tex]\[ f(-2) = (-2)^2 - 2(-2) - 8 = 4 + 4 - 8 = 0 \][/tex]
- Calculate [tex]\( f(4) \)[/tex]:
[tex]\[ f(4) = (4)^2 - 2(4) - 8 = 16 - 8 - 8 = 0 \][/tex]
- Thus, Function B has zeros at [tex]\( x = -2 \)[/tex] and [tex]\( x = 4 \)[/tex].
3. Function C: [tex]\( f(x) = x^2 + 2x - 8 \)[/tex]
- Calculate [tex]\( f(-2) \)[/tex]:
[tex]\[ f(-2) = (-2)^2 + 2(-2) - 8 = 4 - 4 - 8 = -8 \neq 0 \][/tex]
- Calculate [tex]\( f(4) \)[/tex]:
[tex]\[ f(4) = (4)^2 + 2(4) - 8 = 16 + 8 - 8 = 16 \neq 0 \][/tex]
- Thus, Function C does not have zeros at [tex]\( x = -2 \)[/tex] and [tex]\( x = 4 \)[/tex].
4. Function D: [tex]\( f(x) = 2x^2 - 4x - 16 \)[/tex]
- Calculate [tex]\( f(-2) \)[/tex]:
[tex]\[ f(-2) = 2(-2)^2 - 4(-2) - 16 = 2(4) + 8 - 16 = 8 + 8 - 16 = 0 \][/tex]
- Calculate [tex]\( f(4) \)[/tex]:
[tex]\[ f(4) = 2(4)^2 - 4(4) - 16 = 2(16) - 16 - 16 = 32 - 32 = 0 \][/tex]
- Thus, Function D has zeros at [tex]\( x = -2 \)[/tex] and [tex]\( x = 4 \)[/tex].
### Checking the Y-Intercept
To find the y-intercept, we substitute [tex]\( x = 0 \)[/tex] into each function and see if the result equals -16:
1. Function A: [tex]\( f(x) = 2x^2 + 4x - 16 \)[/tex]
[tex]\[ f(0) = 2(0)^2 + 4(0) - 16 = -16 \][/tex]
- Function A has a y-intercept at [tex]\( (0, -16) \)[/tex].
2. Function B: [tex]\( f(x) = x^2 - 2x - 8 \)[/tex]
[tex]\[ f(0) = (0)^2 - 2(0) - 8 = -8 \][/tex]
- Function B does not have a y-intercept at [tex]\( (0, -16) \)[/tex].
3. Function C: [tex]\( f(x) = x^2 + 2x - 8 \)[/tex]
[tex]\[ f(0) = (0)^2 + 2(0) - 8 = -8 \][/tex]
- Function C does not have a y-intercept at [tex]\( (0, -16) \)[/tex].
4. Function D: [tex]\( f(x) = 2x^2 - 4x - 16 \)[/tex]
[tex]\[ f(0) = 2(0)^2 - 4(0) - 16 = -16 \][/tex]
- Function D has a y-intercept at [tex]\( (0, -16) \)[/tex].
### Conclusion
Among the functions, only Function D: [tex]\( f(x) = 2x^2 - 4x - 16 \)[/tex] has the zeros [tex]\( x = -2 \)[/tex] and [tex]\( x = 4 \)[/tex], and the y-intercept at [tex]\( (0, -16) \)[/tex].
Therefore, the correct function is:
[tex]\[ \boxed{2} \][/tex]
### Checking Zero Points
1. Function A: [tex]\( f(x) = 2x^2 + 4x - 16 \)[/tex]
- Calculate [tex]\( f(-2) \)[/tex]:
[tex]\[ f(-2) = 2(-2)^2 + 4(-2) - 16 = 2(4) - 8 - 16 = 8 - 8 - 16 = -16 \neq 0 \][/tex]
- Calculate [tex]\( f(4) \)[/tex]:
[tex]\[ f(4) = 2(4)^2 + 4(4) - 16 = 2(16) + 16 - 16 = 32 + 16 - 16 = 32 \neq 0 \][/tex]
- Thus, Function A does not have zeros at [tex]\( x = -2 \)[/tex] and [tex]\( x = 4 \)[/tex].
2. Function B: [tex]\( f(x) = x^2 - 2x - 8 \)[/tex]
- Calculate [tex]\( f(-2) \)[/tex]:
[tex]\[ f(-2) = (-2)^2 - 2(-2) - 8 = 4 + 4 - 8 = 0 \][/tex]
- Calculate [tex]\( f(4) \)[/tex]:
[tex]\[ f(4) = (4)^2 - 2(4) - 8 = 16 - 8 - 8 = 0 \][/tex]
- Thus, Function B has zeros at [tex]\( x = -2 \)[/tex] and [tex]\( x = 4 \)[/tex].
3. Function C: [tex]\( f(x) = x^2 + 2x - 8 \)[/tex]
- Calculate [tex]\( f(-2) \)[/tex]:
[tex]\[ f(-2) = (-2)^2 + 2(-2) - 8 = 4 - 4 - 8 = -8 \neq 0 \][/tex]
- Calculate [tex]\( f(4) \)[/tex]:
[tex]\[ f(4) = (4)^2 + 2(4) - 8 = 16 + 8 - 8 = 16 \neq 0 \][/tex]
- Thus, Function C does not have zeros at [tex]\( x = -2 \)[/tex] and [tex]\( x = 4 \)[/tex].
4. Function D: [tex]\( f(x) = 2x^2 - 4x - 16 \)[/tex]
- Calculate [tex]\( f(-2) \)[/tex]:
[tex]\[ f(-2) = 2(-2)^2 - 4(-2) - 16 = 2(4) + 8 - 16 = 8 + 8 - 16 = 0 \][/tex]
- Calculate [tex]\( f(4) \)[/tex]:
[tex]\[ f(4) = 2(4)^2 - 4(4) - 16 = 2(16) - 16 - 16 = 32 - 32 = 0 \][/tex]
- Thus, Function D has zeros at [tex]\( x = -2 \)[/tex] and [tex]\( x = 4 \)[/tex].
### Checking the Y-Intercept
To find the y-intercept, we substitute [tex]\( x = 0 \)[/tex] into each function and see if the result equals -16:
1. Function A: [tex]\( f(x) = 2x^2 + 4x - 16 \)[/tex]
[tex]\[ f(0) = 2(0)^2 + 4(0) - 16 = -16 \][/tex]
- Function A has a y-intercept at [tex]\( (0, -16) \)[/tex].
2. Function B: [tex]\( f(x) = x^2 - 2x - 8 \)[/tex]
[tex]\[ f(0) = (0)^2 - 2(0) - 8 = -8 \][/tex]
- Function B does not have a y-intercept at [tex]\( (0, -16) \)[/tex].
3. Function C: [tex]\( f(x) = x^2 + 2x - 8 \)[/tex]
[tex]\[ f(0) = (0)^2 + 2(0) - 8 = -8 \][/tex]
- Function C does not have a y-intercept at [tex]\( (0, -16) \)[/tex].
4. Function D: [tex]\( f(x) = 2x^2 - 4x - 16 \)[/tex]
[tex]\[ f(0) = 2(0)^2 - 4(0) - 16 = -16 \][/tex]
- Function D has a y-intercept at [tex]\( (0, -16) \)[/tex].
### Conclusion
Among the functions, only Function D: [tex]\( f(x) = 2x^2 - 4x - 16 \)[/tex] has the zeros [tex]\( x = -2 \)[/tex] and [tex]\( x = 4 \)[/tex], and the y-intercept at [tex]\( (0, -16) \)[/tex].
Therefore, the correct function is:
[tex]\[ \boxed{2} \][/tex]
Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.